2016
DOI: 10.1002/wcs.1410
|View full text |Cite
|
Sign up to set email alerts
|

Can newborn infants imitate?

Abstract: For several decades, scientists have held that newborn human infants can imitate adult behaviors like mouth opening, tongue protruding, and finger movements. This has been difficult to explain. In particular, it is not clear how newborn infants could know enough about their own bodies and movements, and how these map onto the bodies and movements of others, to be able to match their own felt movements to the seen movements of others. Prominent theories posit the existence of inborn mechanisms that automaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…This behavior is particularly interesting because newborn tongue protruding provides a large part of the evidence purporting to show that newborn human infants can imitate. Newborn imitation, in turn, is particularly interesting because of its implications for our understanding of the origins of knowledge (Jones 2017).…”
Section: W Tecumseh Fitchmentioning
confidence: 99%
“…This behavior is particularly interesting because newborn tongue protruding provides a large part of the evidence purporting to show that newborn human infants can imitate. Newborn imitation, in turn, is particularly interesting because of its implications for our understanding of the origins of knowledge (Jones 2017).…”
Section: W Tecumseh Fitchmentioning
confidence: 99%
“…Opponents have suggested that what looks like an imitative response might be better explained through arousal processes or a coincidental match (Jones, ), an innate releasing mechanism (Anisfeld, ), as based on learning since a neonate does not have the cognitive capacity to “solve the correspondence problem that link self with other for imitation” (Heyes, , p. 6), or as a response dependent on the aerodigestive system (Keven & Akins, ; but see Meltzoff and Simpson et al. for critiques of this view).…”
Section: Introductionmentioning
confidence: 99%
“…Opponents have suggested that what looks like an imitative response might be better explained through arousal processes or a coincidental match (Jones, 1996(Jones, , 2017, an innate releasing mechanism (Anisfeld, 1996), as based on learning since a neonate does not have the cognitive capacity to "solve the correspondence problem that link self with other for imitation" (Heyes, 2016, p. 6), or as a response dependent on the aerodigestive system (Keven & Akins, 2017; but see Meltzoff 2017 andSimpson et al 2017 for critiques of this view). More specifically, Heyes proposes that an associative learning model explains how and why our capacity to imitate develops, whereas Vincini et al (2017) specifies an association by similarity process as most likely to explain early imitation.…”
mentioning
confidence: 99%
“…Although we cannot possibly prove absence, our comprehensive set of null results provides the most compelling form of evidence against neonatal imitation and the like me framework yet. Unless convincing contradictory evidence emerges, developmental psychologists must re‐evaluate the innate and environmental factors that contribute to the emergence of imitation and more complex social cognitive behaviour (Heyes, ; Jones, ; Oostenbroek et al, ).…”
Section: Resultsmentioning
confidence: 99%